Effect of acupoint catgut embedding in chronic fatigue syndrome patients: A protocol for systematic review and meta-analysis. Issue 5 (5th February 2021) - Zhang, Mei-Lin; Fu, Hong-Juan; Tang, Yong; Luo, Zhen-Guo; Li, Jian-Yong; Li, Rui
Abstract: Background: Chronic fatigue syndrome (CFS) is a relatively complex and disabling illness with a substantial economic burden and functional impairment. Until now, many CFS patients lack appropriate healthcare. Acupoint catgut embedding is an effective and emerging alternative therapy for CFE. With this research, we endeavor to investigate the effect and safety of ACE for CFS. Methods: Eight databases will be searched from inception to December 2020: PubMed, EMBASE, The Cochrane Library, Web of Science, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, Chong-Qing VIP database, and Wan-fang database. We regard studies as eligible for inclusion if they were RCTs done in CFS patients, compare acupoint catgut embedding to another treatment strategy, and report fatigue changes at the end of the intervention period. Two independent reviewers complete the study selection, data extraction, and the risk of bias assessment. We assess pooled data using a random-effects model through Revman software (v.5.3) and Stata (version 15.0). Ethics and dissemination: Ethics approval is not required because the individual patient data will not be involved, with no privacy concerns. This systematic review and meta-analysis will provide a reference for CFS patients and clinicians on the non-drug interventions. We will publish and disseminate the results of this review in a peer-reviewed journal or relevant conference. OSF Registration number: 10.17605/OSF.IO/7SHD9 (https://osf.io/7shd9 ).